What rain today?": low students’ questioning skills and The premature use of grammar - Isnawati, Uzlifatul Masruroh; Rahayu, Nanik Sri (English Teaching Journal : A Journal of English Literature, Language and Education, 2024)
This study aims at highlighting students’ ability in formulating questions words in English. This study is intended to make sure that students are able to express question words which enable them to communicate well in English. Therefore, a set of questions were administered and analyzed to identify the student’s ability in developing question words. The study employed 40 student’s English department at the 3rd semester at the odd semester 2022 in Universitas Islam Lamongan. Meanwhile, there were 5 categories of questions asked to the students involving auxiliary verb or yes/no questions. The results showed there were 14 and 11 students answering correctly for auxiliary ‘do’ there were 5 and 6 students correctly answered for question words using auxiliary ‘does. Additionally, there were no correct answer regarding the question using the verb’ rain’. The premature use of grammar and the insufficient knowledge on students’ literacy on the use of question words are identified as the major cause of the students’ difficulty in formulating good questions respectively. Further, there is also the effect of first language interference as well as the insufficient cognitive aspect on related vocabulary use.